Before the mandate: The state of sustainability reporting in the Philippines as seen through reports submitted to Global Reporting Initiatiative (GRI) - So, Real C. (Animo Repository, 2022)
Sustainability reporting is defined as the “information that a company discloses about its environmental impacts and its relationship with its stakeholders by means of relevant communication channels.” With recent scandals attributed to pursuit of profit, businesses are now expected to be transparent about their activities. They are to measure, understand, and communicate their economic, social, and environmental performance through sustainability reports. In the Philippines, the lack of mandate from regulatory agencies has made reporting voluntary and limited. Recently, the Securities and Exchange Commission (SEC) mandated the submission of sustainability reports among publicly listed companies. It also recommended popular platforms for use as guidelines and templates. Prior to the mandate, several Philippines companies have already been regularly or intermittently submitting reports. However, no record of the quantity and quality of these reports is available. The study evaluated reports by Philippines companies submitted to the Global Reporting Initiative (GRI) prior to the SEC mandate. Due to data constraints, the influence of stakeholder salience on reporting cannot be established. Inferences, however, can be derived from data results. Despite differences in reporting within industries, results show that industry type influences reporting content and quality. Earnings per share, as a performance in indicator, was found to exert no influence on reporting content and quality. The results provide a picture of the state of sustainability reporting in the Philippines, as well as insights for future projections in reporting.